Surgical Interventions Are Effective for Treating Unruptured Sinus of Valsalva Aneurysms - Qiu, Juntao; Xie, Enzehua; Wang, Yuetang; Wang, Wei; Yu, Cuntao; Luo, Xinjin (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT Background: This study investigates the optimal management for unruptured sinus of Valsalva aneurysms (USVAs) combined with other cardiovascular lesions. Methods: This retrospective study examined 33 USVA patients who underwent surgical repair from February 1, 2007 to January 31, 2012. We analyzed the surgical procedures and the patients’ quality of life after surgery. Additionally, echocardiography follow-up was performed before and after the operation. Results: Most USVAs(87.8%) originated in the right coronary sinus. Aside from one patient who was preoperatively misdiagnosed as having a ruptured sinus of Valsalva aneurysm (SVA). USVAs of the right coronary sinus were addressed by reinforcing this sinus with a Dacron patch through the right ventricle. USVAs were corrected by aortotomy using an autogenous pericardium patch when they originated in the non-coronary or left coronary sinus. Thirty patients (90.9%) were followed up for 22–119 months. No early death, residual fistula or SVA recurrence were found during the follow-up period. They all had a good quality of life and good heart function (New York Heart Association class I-II). Conclusions: Active surgical repair of an USVA can be achieved with satisfactory results in patients combined with other cardiovascular lesions.